Personal Political Branding to Increase Electability: Regional Head Candidates in Pemalang 2024 - Kusuma, Muhamad Edgar; Zainudin, Arif; Widodo, Agus (International Journal of Research and Community Empowerment, 2025)
Social media's increasing impact on local politics has made personal political branding crucial to preserving democracy and raising political literacy. It is crucial for theory and practice to comprehend how such branding affects public perception in the context of regional elections. In this study, the impact of personal branding on Pemalang Regional Head candidates will be examined, with particular attention paid to the phenomenon of branding and political mediatization, in which non-political public figures run for office and acquire legitimacy through digital engagement and personal branding. The study used a qualitative-descriptive approach and gathered information from Vicky Prasetyo's official Instagram account. To evaluate public responses, interaction levels, and thematic content trends, Orange Data Mining software was used in conjunction with a Naïve Bayes sentiment analysis model. According to the findings, personal branding tactics that prioritize visual performativity, emotional intimacy, and endorsements from other public figures result in a preponderance of neutral feeling, which reflects the uncertainty of public perception. According to the study's findings, personal branding in this instance offers electability engagement and symbolic visibility, but it lacks a coherent and substantial policy program narrative. These results illustrate the potential of social media data as an alternate electability metric and lend theoretical support to local political communication research. In practice, the findings can help electoral management organizations, campaign consultants, and political practitioners create more focused digital campaign strategies and regulations that adapt to the dynamics of online political communication, enhancing the quality of democracy and raising citizen political literacy.